Risk Analysis of Community Based Infrastructure Grant Program - Sasono, Muhammad Ermando Nurman; Arif Rohman, Mohammad (Institut Teknologi Sepuluh Nopember, 2020)
The Provincial Government of East Java seeks to improve the welfare of the community and overcome socio-economic problems through local grant-making mechanisms. One form of grants carried out by the Administration of Development Bureau (ADB) is road infrastructure development. The implementation of the project has risks that have an impact on the use of ineffective and inefficient regional budget (APBD). Risks obtained from literature which were analyzed to determine the effect of these risks on the sustainability of the program. The Differential Semantic Scale questionnaire was conducted first to assess the relevance of risk to the implementation of the regional grant program. The next step is Risk Level Analysis. At this stage the probability and impact calculation of each risk is carried out. The questionnaire was used to obtain respondents opinion who were responsible for the implementation of the regional grant program. 3 risks have been generated which are included in the high risk level of 26 relevant risks. ADB needs to pay attention to risks, especially priority risks in the management of infrastruture grant program. The findings in this study provide new references in the field of risk management.